Ward round documentation in gastroenterology; can we improve patient safety? - Deborah Charlesworth-Benedict; Rahavei Ragunathan (Future Healthcare Journal, 2025)
Background: Structured ward rounds are key to coordinate assessments and manage patients safely and efficiently. The effectiveness of ward rounds is often affected by challenges such as clinical priorities, a lack of staff and inadequate planning when structuring the ward round documentation. Within the gastroenterology unit, ward rounds can proceed rapidly and patients are often located in various outlier wards. Therefore, it is important that all aspects of patient care are addressed in the ward round documentation. Aim: The Royal College of Physicians (RCP) created a guidance highlighting the importance of ward round documentation, with a standardised checklist.1 This quality improvement project aimed to introduce a structured ward round auto-text template to improve ward round documentation within the gastroenterology department using the parameters laid out in the RCP guidance, thus improving patient care and safety. Method: Ward round documentation within the gastroenterology department at Countess of Chester Hospital was reviewed, in accordance with the guidance laid out by the RCP.1 The ward round entries for 20 patients were analysed against the 12 parameters from the RCP checklist. An auto text was then created on CERNER (the electronic patient record) to form the ward round documentation template. A poster outlining this auto-text template with instructions on how to use it were developed and attached to the computers on the ward. An email with instructions was also sent to all doctors. An audit of another 20 patients was performed 2 months after implementation to identify any improvement. Results: Within this first audit cycle, improved adherence to the RCP guidance checklist was seen (pre-template = 23% vs post-template 38%). Documentation of allergies remained the same because this parameter was a mandatory field in CERNER. Following the introduction of this auto-text template, documentation of review for most categories (venous thromboembolism, drug chart, antibiotics and observation charts) increased by 5–30%. Documentation of investigations (bloods, scans, etc) reviewed, improved from 50% to 85%. Conclusion: This project highlighted areas within our ward round documentation that needed improvement. An auto-text ward round template was created and implemented in CERNER. Overall, there was improved patient care with the potential to reach the 100% target. This quality improvement project can also be implemented across other medical specialties and trusts. Six months after implementation, a further audit and intervention are planned to ensure sustainable improvement.